2022
DOI: 10.3390/foods11162524
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Critical Review on TNF-α as a Potential Inflammatory Biomarker Responsive to Dietary Intervention with Bioactive Foods and Derived Products

Abstract: This review collects and critically examines data on the levels of tumour necrosis factor-alpha (TNF-α) in lean, overweight and obese subjects, and the effects of intervention with different foods and food products containing bioactive constituents in overweight/obese individuals. We additionally explore the influence of different single nucleotide polymorphisms (SNPs) on TNF-α levels and compare the response to food products with that to some anti-obesity drugs. Our aim was to provide an overview of the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 186 publications
0
4
0
Order By: Relevance
“…TNF-α is a biomarker of systemic inflammation [3][4][5]; therefore, the fact that its level was lower in the T1D group could indicate no chronic inflammation. Nevertheless, this observation is based on the mean value and 22.2% of T1D participants (n = 2) were found with resting TNF-α of >50.0 pg/mL, which indicated a rather high level of inflammation when compared with the normal range of the cytokine observed in individuals without inflammatory diseases [104,105]. TNF-α is amongst the main pro-inflammatory cytokines implicated in the inflammation of the pancreatic beta cells [106]; hence, its elevated level is to be expected in T1D patients.…”
Section: Discussionmentioning
confidence: 84%
“…TNF-α is a biomarker of systemic inflammation [3][4][5]; therefore, the fact that its level was lower in the T1D group could indicate no chronic inflammation. Nevertheless, this observation is based on the mean value and 22.2% of T1D participants (n = 2) were found with resting TNF-α of >50.0 pg/mL, which indicated a rather high level of inflammation when compared with the normal range of the cytokine observed in individuals without inflammatory diseases [104,105]. TNF-α is amongst the main pro-inflammatory cytokines implicated in the inflammation of the pancreatic beta cells [106]; hence, its elevated level is to be expected in T1D patients.…”
Section: Discussionmentioning
confidence: 84%
“…TNF-α is an activator of the production of different cytokines, promoting a pro-inflammatory state. In general, long-term elevated TNF-α levels are associated with conditions such as inflammatory bowel disease, and lowering the levels of this cytokine is generally considered to have a beneficial anti-inflammatory effect [ 36 , 37 , 38 ]. A previous study characterized the chia phenolic extract and found that the main phenolic compounds in the extract were rosmarinic acid, danshensu glycoside, ferulic acid, and caffeic acid [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been intriguing genetic research showing the benefit of vitamin D and phytochemicals in the remission of inflammatory bowel disease [89]. In a dietary intervention study, they were found to downregulate the level of TNF-α, an important factor in chronic inflammation [90].…”
Section: Health Promotion Effect Of Vitamin D and Interactions With P...mentioning
confidence: 99%